Differences in Pulse Rate of Mineral Water and Natural Cyclic Drink (Young Coconut Water) After 1600m Run - Muhammad Rizki Rahmadiansyah; Rubiyatno; Putra Sastaman (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The purpose of this study was to test the difference between coconut water and mineral water on the effect of dehydration speed.  The effectiveness of this liquid is still a question mark among sportsmen. The research method used experiments with 20 people as a sample consisting of 10 people per group. First of all, the initial pulse measurement was carried out then warmed up and ran for 1600 meters. The first group after finishing was given 250 ml of coconut water and 5 minutes after checking the pulse rate, as well as the second group with the same dose but given mineral water. Data were analyzed with non-parametric tests. The results of the non-parametric test explained that there was no difference between the administration of mineral water and coconut water on the achievement of the pulse rate after 5 minutes.